Criminal Customary Of Baduy Society - Endah Lestari Dwirokhmeiti; Woro Winandi; Shinta Ayu Purnamawati (LPPM of NAROTAMA UNIVERSITY, 2018)
The existence of Baduy community in Lebak Regency is classified into 3 (three) groups, namely: a. Inner Baduy (Urang Kanekes); b. Outer Baduy (Urang Panamping); c. Baduy Dangka. In general, it can be described that the first group called the Baduy Dalam (Urang Kanekes) community is a society that obeys the entire rules or rules set by Pu'un (Kepala Adat). Baduy Dalam community lives in 3 (three) villages of Cibeo, Cikartawana, and Cikeusik. Related to the custom law in Baduy Dalam, for its adherents there is the enforcement of customary law, that is with the enforcement of customary criminal law for the offenders are subject to strict sanctions.One is the customary criminal society Baduy Dalam which provides social crime penalties for the community Banduy In violation of customary law. Philosophically Social work penalty is in harmony with the fifth principle of Pancasila, which is social justice for all the people of Indonesia, in which the value of hard work is included. In carrying out the social work crime, the convicted person is required to work hard in serving the crime. Social work crime is the